2006
DOI: 10.1037/0002-9432.76.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Campus mental health services: Recommendations for change.

Abstract: College officials indicate that the number of students with serious mental illnesses has risen significantly. Recent media attention surrounding several high profile suicides has opened discussion of mental illness on campus. The authors summarize literature on college students and mental illness, including barriers to service receipt. Recommendations to improve campus-based responses to serious mental illness are presented on the basis of well-accepted service principles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
224
0
17

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(247 citation statements)
references
References 44 publications
6
224
0
17
Order By: Relevance
“…13,14,17 Although they may be few in number, students with serious mental health illness or psychological problems are highly demanding in terms of staff time and resources and they are especially challenging to campus mental health services. 2,15 A recent study suggested that campus mental health services can possibly reduce the delay between the onset of psychiatric conditions and its proper treatment. In addition, it should be noticed that mental health status in young adulthood is associated with substance use, academic problems and other detrimental social outcomes later in life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14,17 Although they may be few in number, students with serious mental health illness or psychological problems are highly demanding in terms of staff time and resources and they are especially challenging to campus mental health services. 2,15 A recent study suggested that campus mental health services can possibly reduce the delay between the onset of psychiatric conditions and its proper treatment. In addition, it should be noticed that mental health status in young adulthood is associated with substance use, academic problems and other detrimental social outcomes later in life.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it should be noted that many young adults experience their first psychiatric episode during their time at university, considering that epidemiological studies indicate that many mental illnesses usually have their onset in young adulthood. 2 More recently, the mental health of postgraduate students has also gained attention and studies have been reporting high prevalence of depression, distress and burnout among postgraduates. [3][4][5] In the 1950s, many campus counseling/ mental health services were founded in universities in the United States and Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos epidemiológicos têm revelado que transtornos mentais têm maior chance de surgir pela primeira vez no início da vida adulta, principalmente no período universitário (Cerchiari, 2004;Mowbray et al, 2006). As situações de perda presentes no desenvolvimento normal acentuam-se quando os jovens ingressam na universidade, pois afastam-se de um círculo conhecido de relacionamentos familiares e sociais, o que pode desencadear situações de crise (Fernandes e Rodrigues, 1993;Cechiari, 2004).…”
Section: Introductionunclassified
“…College students with higher perceived psychological distress were less likely to persist towards graduation (Kitzrow, 2009). The perceived responsiveness of the institution, i.e., how/when it takes care of/attends to its' students, may be acutely significant when a student feels vulnerable and in need of help (Mowbray et al, 2006). For such a student, the UCC therapist can partially represent the institution, and the therapeutic alliance, i.e., collaborative and affective bond between therapist and patient, has been shown to affect subsequent treatment improvement (Bergin & Garfield, 2013).…”
Section: Correlates Of Institutional Commitmentmentioning
confidence: 99%